1971
DOI: 10.1128/jvi.7.6.726-735.1971
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Ribonucleic Acid Polymerases of Two Rhabdoviruses, Kern Canyon Virus and Vesicular Stomatitis Virus

Abstract: A ribonucleic acid (RNA)-dependent RNA polymerase has been demonstrated in Kern Canyon virus (KCV) particles. The RNA product of the KCV polymerase hybridizes to KCV viral RNA. The properties of this viral enzyme have been characterized and compared with those of vesicular stomatitis virus (VSV). RNA polymerases from both viruses require similar conditions of temperature, pH, and detergent and magnesium concentrations for maximal synthesis of RNA. The RNA polymerase contained in the virion of KCV was more depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
29
0

Year Published

1972
1972
1980
1980

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 15 publications
4
29
0
Order By: Relevance
“…Of the nonrabies serogroup rhabdoviruses, the origin and cultivation in BHK-21 cells of Kern Canyon virus (28) have been previously described (1). Hart Park (Flanders) virus (27,40) was obtained as suckling mouse brain suspension from the Center for Disease Control.…”
mentioning
confidence: 99%
“…Of the nonrabies serogroup rhabdoviruses, the origin and cultivation in BHK-21 cells of Kern Canyon virus (28) have been previously described (1). Hart Park (Flanders) virus (27,40) was obtained as suckling mouse brain suspension from the Center for Disease Control.…”
mentioning
confidence: 99%
“…The virion-associated ribonucleic acid (RNA)dependent RNA polymerase of complete infectious vesicular stomatitis virus (VSV-1) is responsible for transcribing the virion genome and making complementary messenger RNA species (2, 10, 15). In vitro this transcription process is repetitive, optimal around 31 C, and continues for many hours, although it takes about 60 to 90 min to yield a complete complement of product RNA molecules (1,3). At 37 C, the in vitro transcription is slower, incomplete (terminating between 60 and 90 min of incubation), and, although it is repetitive, only about 30% of the genome is transcribed (6,7).…”
mentioning
confidence: 99%
“…Method 3. Virus was precipitated by the ammonium sulfate method of Aaslestad et al (1). Calf serum (to 2%, v/v) and ammonium sulfate (30%, w/v) were then added as co-precipitants for the virus.…”
Section: Methodsmentioning
confidence: 99%
“…After inactivation with fl-propiolactone (BPL), these virus concentrates have proven to be potent vaccines (21). We have also found that rabies virus and other rhabdoviruses may be efficiently concentrated by ammonium sulfate precipitation (1). Recently Schneider et al (11) used the aluminum phosphate gel adsorption technique (9) to concentrate and purify rabies virus.…”
mentioning
confidence: 99%